2020
DOI: 10.1186/s12935-020-01414-5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the expression of sodium/potassium-ATPase α subunits and prognosis of ovarian serous cystadenocarcinoma

Abstract: Background: Ovarian serous cystadenocarcinoma (OSC) is the most common and lethal gynecological cancer in women worldwide; however, biomarkers to diagnose and predict prognosis of OSC remain limited. Therefore, the present study aimed to investigate whether sodium/potassium adenosine triphosphate (Na + /K +-ATP)ase α-subunits (ATP1As) are helpful diagnostic and prognostic markers of OSC. Methods: Gene expression data (RNA-Seq) of 376 patients with OSC were downloaded from The Cancer Genome Atlas (TCGA) program… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
3
5
0
Order By: Relevance
“…We found that the activity of this pump in cancer tissues was about 20% higher than in control samples, but this increase was not statistically significant. However, observed tendency to increasing the activity of Na + /K + ATPase in cancer is in agreement with findings of other authors, showing that the baseline expression and activity of Na + /K + ATPase were enhanced in breast cancer, compared to a non-tumorigenic breast cell line [ 21 ], in patients with ovarian serous cystadenocarcinoma [ 22 ]. In samples of patients’ colorectal cancer, highly expressed Na + /K + ATPase isozymes were found [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…We found that the activity of this pump in cancer tissues was about 20% higher than in control samples, but this increase was not statistically significant. However, observed tendency to increasing the activity of Na + /K + ATPase in cancer is in agreement with findings of other authors, showing that the baseline expression and activity of Na + /K + ATPase were enhanced in breast cancer, compared to a non-tumorigenic breast cell line [ 21 ], in patients with ovarian serous cystadenocarcinoma [ 22 ]. In samples of patients’ colorectal cancer, highly expressed Na + /K + ATPase isozymes were found [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previously, ATP1A2 expression was found to be downregulated in breast cancer [ 28 ]. Another evidence for the participation of ATP1A2 in ovarian serous cystadenocarcinoma pathophysiology comes from Huang et al, which revealed that the expression of ATP1A2 was higher in adjacent normal bladder tissues than in tumor tissues [ 29 ]. Additionally, Zhang et al found that ATP1A2 was regulated by the lncRNA FLJ42875 in laryngeal squamous cell carcinoma [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Huang et al reported that the overexpression of ATP1A2 may be related to the poor prognosis of advanced ovarian cancer. 16 Moreover, (+)-Strebloside, a cardiac glycoside that inhibits the activity of Na + /K + -ATPase, inhibits p53 expression and NF-κB activity, inducing ovarian cancer cell apoptosis and impairing its proliferation. 17 Another evidence for the participation of Na + /K + -ATPase in ovarian cancer pathophysiology comes from Tummala et al, which revealed…”
Section: Discussionmentioning
confidence: 99%